Validation of a Chinese Version of the Parental Burnout Assessment - Cheng, Huabin; Wang, Wei; Wang, Shengnan; Li, Yimin; Liu, Xia; Li, Yongxin (Frontiers in Psychology, 2020)
Parenting is a meaningful endeavor but it also induces stress, which can cause parental burnout. In China, the assessment and study of parental burnout is still in its formative stages. To contribute to advancing this field, the present study aimed to develop and validate a Chinese version of the Parental Burnout Assessment (PBA). Questionnaires were distributed to 614 families (comprising students in the eighth grade and both of their parents; one questionnaire for each person) on two separate occasions (Time 1 and Time 2). The students were asked to self-report their loneliness and life satisfaction at Time 1, and their anti-social behavior at Time 2. Meanwhile, parents were asked to self-report their parental burnout and job burnout at both Time 1 and Time 2, their marriage satisfaction at Time 1, and their levels of agreeableness and neuroticism at Time 2. Using the data obtained, we performed exploratory and confirmatory factor analyses, which indicated that this version of the PBA had a single-factor structure. The α of the PBA was .938 at Time 1 and .952 at Time 2. At Time 1, parental burnout was positively related to their job burnout in emotional exhaustion and depersonalization, and negatively related to their marriage satisfaction. In addition, parental burnout was positively related to students’ life satisfaction, and mothers’ parental burnout was positively related to students’ loneliness. At Time 2, parental burnout showed positive relations with neuroticism and job burnout through emotional exhaustion and depersonalization, and was negatively related to agreeableness. In addition, mothers’ parental burnout was positively related to students’ anti-social behavior. Furthermore, parental burnout at Time 1 also showed positive relations with job burnout through emotional exhaustion and depersonalization measured at Time 2, and parental burnout at Time 1 was positively related to students’ anti-social behavior at Time 2. Overall, the present study confirmed the reliability and validity of the Chinese version of the PBA.